Partnerships in mental healthcare service delivery in low-resource settings: developing an innovative network in rural Nepal. Issue 1 (December 2017) - Acharya, Bibhav; Maru, Duncan; Schwarz, Ryan; Citrin, David; Tenpa, Jasmine; Hirachan, Soniya; Basnet, Madhur; Thapa, Poshan; Swar, Sikhar; Halliday, Scott; Kohrt, Brandon; Luitel, Nagendra; et al.
Abstract Background Mental illnesses are the largest contributors to the global burden of non-communicable diseases. However, there is extremely limited access to high quality, culturally-sensitive, and contextually-appropriate mental healthcare services. This situation persists despite the availability of interventions with proven efficacy to improve patient outcomes. A partnerships network is necessary for successful program adaptation and implementation. Partnerships network We describe our partnerships network as a case example that addresses challenges in delivering mental healthcare and which can serve as a model for similar settings. Our perspectives are informed from integrating mental healthcare services within a rural public hospital in Nepal. Our approach includes training and supervising generalist health workers by off-site psychiatrists. This is made possible by complementing the strengths and weaknesses of the various groups involved: the public sector, a non-profit organization that provides general healthcare services and one that specializes in mental health, a community advisory board, academic centers in high- and low-income countries, and bicultural professionals from the diaspora community. Conclusions We propose a partnerships model to assist implementation of promising programs to expand access to mental healthcare in low- resource settings. We describe the success and limitations of our current partners in a mental health program in rural Nepal.